Pemantauan Tumbuh Kembang Bayi dan Balita Berbasis Tehnologi Informasi di Posyandu Kelurahan Linggasari Kabupaten Ciamis - Neli Sunarni; Resna Litasari; Tasya Furriha Khoerussabila; Annisa Tsania Rizqiyani (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Introduction: Monitoring a child's growth and development in the first 1,000 days is very important considering the rapid growth and development of children at that age. One way to monitor children's growth and development is by carrying out posyandu activities. In implementing posyandu, there are often obstacles for posyandu cadres in recording and reporting. Technological developments can make it easier to make the recording and reporting process more practical and efficient. Objective: The aim of this activity is to increase the empowerment of cadres in recording the growth and development of infants and toddlers through Android-based infants and toddler growth information technology applications. Method: This community service activity was carried out at the Linggasari Village Pustu with 18 cadres as respondents. The stages of this activity include planning, analysis, design, implementation, system testing, preparation for implementation, implementation and use of information technology that has been designed. Result: The results of this community service show that posyandu cadres can easily access information on the growth and development of babies and toddlers in Linggasari Village, making posyandu activities more effective and efficient. Conclusion: Android-based infants and toddler growth and development applications can help posyandu cadres in recording and reporting, and make posyandu activities more effective.